The Implementation of Adult Learning Assumption Readiness Relationships in Improving the Effectiveness of Learning Process - Muslikhah, Muslikhah -; Kamil, Mustofa; Kamarubiani, Nike (Universitas Negeri Semarang, 2018)
Poverty is a social problem that is always present in society, especially in developing countries. The purpose of this research is to know/see the learning effectiveness of family development session program within the participants’ preparation in Kebon Jayanti urban village. The type of research that used is survey research. The research approach is done by survey method, combined with qualitative to explore in-depth information of gained situation in this survey research. The results of this study indicate that companion has a role as an agent that posts positive inputs and directives based on their knowledge and experience. FDS participants are also expected to exchange ideas with existing knowledge and experience under guidance or counseling to raise public awareness, share information, and enhance family development session comprehension. Thus, the conclusion is as follows; the application of learning readiness assumption in improving the learning process of family development session is well, due to the consideration of learning process with basic assumption of an adult, learning method, and interaction between facilitator and learning community in both directions while delivering materials for family development session